Analisis Pendapatan Asli Daerah Melalui Kontribusi Pajak Bumi Dan Bangunan Dalam Meninjau Peraturan Daerah Kabupaten Pamekasan - Kamaroellah, R. Agoes (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2023)
Rural and urban land and building tax or PBB-P2 is a regional tax as a source of original regional income. The aim of this research is to determine the contribution of Regional Tax and Land and Building Tax to local original income in accordance with Pamekasan Regency regional regulations. This research uses quantitative descriptive methods. This research looks at the contribution of regional taxes and land and building taxes to Original Regional Income (PAD) from 2016-2020. The results of this research show that regional taxes and land and building taxes make a very good contribution to PAD. Therefore, the role of regional taxes and PBB (P2) is needed in increasing PAD which is realized in regional regulations. Regional tax collection officers provide services by increasing the means of paying regional taxes so that the potential for regional tax revenues increases. The revenue department maintains a good relationship with collection officers so that they can supervise local tax collection to avoid fraud during collection.